2000
DOI: 10.1038/sj.bmt.1702542
|View full text |Cite
|
Sign up to set email alerts
|

A low CD34+ cell dose results in higher mortality and poorer survival after blood or marrow stem cell transplantation from HLA-identical siblings: should 2 × 106 CD34+ cells/kg be considered the minimum threshold?

Abstract: Summary:We studied the effect of the CD34 ؉ cell dose on transplant-related mortality (TRM) and survival in 39 patients randomized to receive lenograstim-mobilized PBSCT (n = 20) or BMT (n = 19) from HLA-identical siblings. Both marrow and blood were harvested, and one infused in a double-blind fashion. The median nucleated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 29 publications
(24 reference statements)
4
84
2
Order By: Relevance
“…[1][2][3] Results from some studies furthermore suggested that a relatively low CD34 þ cell dose, between 2 Â 10 6 and 4 Â 10 6 per kg of patient body weight, is the minimum required for rapid or durable engraftment. 22 In contrast, Slowman et al 23 found that grafts with more CD34 cells were not associated with faster neutrophil engraftment, and other clinical analyses support …”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3] Results from some studies furthermore suggested that a relatively low CD34 þ cell dose, between 2 Â 10 6 and 4 Â 10 6 per kg of patient body weight, is the minimum required for rapid or durable engraftment. 22 In contrast, Slowman et al 23 found that grafts with more CD34 cells were not associated with faster neutrophil engraftment, and other clinical analyses support …”
Section: Discussionmentioning
confidence: 88%
“…5,6 As observed in both animal and human studies, G-CSF induces IL-4 and IL-10 production in peripheral T cells (that is, the TH2 lymphokine profile) instead of TH1-polarized proinflammatory cytokines; in addition, G-CSF induces a reduction in the total number of BM T cells and reverses the CD4 þ /CD8 þ ratio. [18][19][20][21] Although some conflicting data have been reported, the majority of studies agree that pBM or sBM SCT reduces the incidence of chronic GVHD compared to PBSCT. 6,7,9 Thus, considering both in vitro and clinical findings regarding acute and chronic GVHD, pBM appears to be an appropriate stem cell source for use in patients with critical comorbidities because it is less likely to result in chronic GVHD.…”
Section: Cause Of Deathmentioning
confidence: 99%
“…According to the literature, several G-CSF regimens have been used to stimulate BM, ranging from 2-to 5-day priming periods at doses of 3À10 mg/kg per day. [3][4][5][6]18 Our modified G-CSF regimen was chosen based on previous data indicating that two doses (that is, DÀ2 and DÀ1) produce sufficient CD34 þ and CD3 þ cells to allow rapid engraftment with modest transfusion requirements and a decrease in hospitalization by a mean of 10 days. 3 The CD34 þ and CD3 þ cell contents per kilogram recipient body weight were comparable with values observed in previous studies.…”
Section: Cause Of Deathmentioning
confidence: 99%
“…In the same year, Singhal et al recommended a CD34 þ dose of 2 Â 10 6 /kg as the minimum threshold for allogeneic sibling blood or marrow SCT. 3 Two years later, Bittencourt et al concluded that a CD34 þ dose of 3 Â 10 6 /kg was optimal for allogeneic BMT in terms of faster engraftment, decreased treatment-related mortality and increased OS. 4 Allo-SCT is a potentially curative therapeutic option for aplastic anaemia (AA).…”
Section: Introductionmentioning
confidence: 99%